Monetary Finance : Do Not Touch, or Handle with Care? - Agur, Itai (Departmental Papers; Departmental Paper, 2022)
This paper reviews the theoretical arguments in favor and against MF and presents an empirical assessment of the risks that it may pose for inflation.